PENGARUH KEMANDIRIAN BELAJAR DAN BIMBINGAN BELAJAR TERHADAP KEMAMPUAN MEMAHAMI JURNAL PENYESUAIAN PADA SISWA SMA MELATI PERBAUNGAN - Dedi Syahputra (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2017)
Economic subjects is one of the difficult subjects requiring study interest of students so it's no wonder the learning pretasi students are categorized as low. This is because the student's mastery against economic subjects can be seen from the ability of memorize in understanding. The purpose of this research is to know the influence independence study and tutoring toward the ability to understand the adjustments on journals high school student Jasmine Perbaungan. Type of this research is quantitative. The population in this research is the entire high school student majoring in Social Science as much as 47 people and the sample is total population. The analysis of the data used in this research is a multiple regression test. The research results obtained: independence of the study (p = 0.002), tutoring (p = 0.001) and partially (p = 0.000) influence on the ability to understand the adjustment journal.